Genetic diversity of antagonistic bacterial isolates obtained from Theobroma cacao L. to control Fusarium oxysporum f. sp. cubense race 1 - Canchignia-Martínez, Hayron Fabricio (2025)
The banana (Musa AAA) is affected by Fusarium oxysporum f. sp. cubense, which causes discoloration in the xylem duct, leading to terminal wilting. The use of plant growth promoting rhizobacteria (PGPR) as a biological control produces different antagonistic compounds and inhibits the growth of various phytopathogens. The objective of the study was based on the molecular identification of rhizobacteria that produce phytohormones with biocontrol activity against Foc-R1. The presence of the 225 bp ChiA gene was observed in PGPR. Phylogenetic analysis of 16S rRNA by sequencing and ERIC-PCR showed genetic variability with the formation of four subgroups. Molecular identification by sequencing the 16S rRNA gene defined the genera as Klebsiella, Enterobacter, and Pseudomonas. There is variation in the biosynthesis of the phytohormones AIA, AG, and AS in strains MH-18, W-417, and FZ 9-7 at 72 h. The identification of Foc-R1 by PCR shows an amplicon of 350 bp. Antagonistic assays of bacterial supernatants from strain FZ 9-7 show 71% mycelial inhibition of Foc-R1 and a decrease in spore production of 2.5X106 spores mL-1. The results provide information on the genetic relationships of PGPRs through the production of secondary metabolites such as proteases, catalases, chitinases, and siderophores, as well as morphological and molecular analysis for the identification of Foc-R1 and its interaction with antagonistic extracts in inhibiting the growth of diseases in bananas and cocoa.